1978
DOI: 10.1093/oxfordjournals.jbchem.a132166
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Urinary β-Aspartyl Dipeptides and Their Concentrations in Human Urine

Abstract: beta-Aspartyl-methionine, -aspartic acid and -glutamic acid and gamma-glutamyl-threonine and -glycine were isolated and identified in human urine by ion-exchange chromatography, high-voltage paper electrophoresis, acid hydrolysis and determination of N-terminal amino acids of the isolated compounds, and comparison of their behaviors in paper electrophoresis and chromatography with those of the authentic compounds. The concentrations of acidic beta-aspartyl dipeptides in human urine were determined using an ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Few peptidases cleave isoaspartyl bonds, but proteolysis of the surrounding residues creates isoaspartyl-containing dipeptides and tripeptides that can be excreted in the urine (33)(34)(35)(36). Thus, if mice lacking endogenous PCMT1 do not have another repair pathway, they might excrete the damaged residues that are normally repaired in the cells of wild-type mice.…”
Section: Accumulation Of Damaged Aspartyl Residues In Brainmentioning
confidence: 99%
“…Few peptidases cleave isoaspartyl bonds, but proteolysis of the surrounding residues creates isoaspartyl-containing dipeptides and tripeptides that can be excreted in the urine (33)(34)(35)(36). Thus, if mice lacking endogenous PCMT1 do not have another repair pathway, they might excrete the damaged residues that are normally repaired in the cells of wild-type mice.…”
Section: Accumulation Of Damaged Aspartyl Residues In Brainmentioning
confidence: 99%
“…It is not known whether the aspartic acid in the acidic peptides isolated from calf brain synaptic vesicles (Lahdesmaki et al, 1977;Marnela and Lahdesmaki, 1983) are in the a-or P-configuration. On the other hand, P-DG and various other p-aspartylpeptides have been identified previously in human urine and in rat cecal contents (Buchanan et al, 1962;Lou, 1975;Tanaka and Nakajima, 1978;Welling, 1982), but have not been found in more than trace amounts in tissues. In rats the amount of cecal P-DG decreased when animals were maintained under germ-free conditions, and its formation was directly associated with intestinal flora (Welling and Groen, 1978).…”
Section: Discussionmentioning
confidence: 93%
“…Urine contains a low concentration of aspartate, primarily in peptides ( 50 ). IsoAsp-containing peptides have also been detected in urine ( 51 ). Moreover, it was reported that the pcm gene is induced in UPEC CFT073 strain during infection of mouse urinary tract ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is especially significant in environments where the primary source of aspartate is the catabolism of environmental peptides, some of which contain IsoAsp. These conditions are observed when E. coli grows in complex media, such as LB, and in natural environments such as the host urinary tract (50,51,(60)(61)(62). For instance, in human urine, the Pcmmediated aspartate salvaged from IsoAsp would increase the amount of aspartate available for cellular functioning by up to 40% (51,62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation